Analisis Biomekanika Gerak Pukulan Jarak Jauh Pada Atlet Woodball Univeritas Negeri Semarang - Hanif Putra Toma; Fajar Awang Irawan (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
Blow distance (long stroke) is one type of punch that is used on the fairway up to 130 m. A long-range shot that is right on target where the ball must move as far as possible as close as possible to the gate from the starting area and not out of the fairway or track. The type of research used is descriptive quantitative. The sample in this study was 8 athletes at the Woodball State University of Semrang. This research uses Kinovea software version 0.8 as a data analysis technique.Based on the results of the study the average time required was 2.07 s, mallet distance 1.70 m, average punching speed 0.83, average toe angle of 164.83°, elbow flexion angle of 164.14°.The results of the study show that the range of long-distance strokes performed by the Semarang State University woodball athletes is in the criteria of "appropriate", "effective enough", and "quite efficient".